2011
DOI: 10.1179/2042645311y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal modification on mechanical properties of Canadian white birch (Betula papyrifera)

Abstract: Wood is a renewable material widely used in the construction industry. However, it is susceptible to fungal degradation. Several chemical products have been developed to improve its durability, but the toxicity of some of these products limits their use. One alternative to chemical treatment is thermal modification of wood. This method improves the dimensional stability of wood and reduces its susceptibility to decay. The impact of different parameters (maximum temperature, heating rate, holding time, and gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
2
7
0
5
Order By: Relevance
“…While the MOE increases slightly between 190 and 200°C and decreases slightly at 210°C. Similar results were found in the literature with other species (Bekhta and Niemz 2003, Pavlo et al 2003, Poncsák et al 2006, Metsa-Kortelainen and Viitanen 2010, Lekounougou et al 2011). They found that the MOR decreases when the thermal modification temperature increases, while the MOE does not appear to be significantly affected by temperature.…”
Section: Resultssupporting
confidence: 92%
“…While the MOE increases slightly between 190 and 200°C and decreases slightly at 210°C. Similar results were found in the literature with other species (Bekhta and Niemz 2003, Pavlo et al 2003, Poncsák et al 2006, Metsa-Kortelainen and Viitanen 2010, Lekounougou et al 2011). They found that the MOR decreases when the thermal modification temperature increases, while the MOE does not appear to be significantly affected by temperature.…”
Section: Resultssupporting
confidence: 92%
“…In the closed system the decrease in MOE is directly correlated to the CML, but in the open system modification there was an increase of the MOE ratio until 200°C reaching 1,2 (CML 15%), after that point it started to decrease but without showing a direct relation between the CML and the MOE. Similar peaks of MOE have been reported in other species, such as Canadian white birch (Lekounougou et al 2011), Picea abies (Norway spruce) (Borrega and Kärenlampi 2008) and other eucalypt species, such as E. grandis and E. regnans (de Cademartori et al 2015), and E. globulus (Santos 2000), although no type of treatment was mentioned in the latter.…”
Section: Static and Dynamic Mechanical Propertiessupporting
confidence: 80%
“…In both species, MOE and MOR reduced with rising modification temperature. However, other authors showed that MOE of thermally modified wood can de higher than the reference values increased in certain thermal modifications (Borrega and Kärenlampi 2008, Kubojima et al 2000, Lekounougou et al 2011, Rautkari and Hill 2014, Santos 2000. The structural integrity of wood is also affected by the thermal modification, as the degradation of hemicelluloses (Alen et al 2002, Boonstra and Tjeerdsma 2006, Sundqvist et al 2006 can cause an increased brittleness of the material (Phuong et al 2007, Weigl et al 2012.…”
Section: Introductionmentioning
confidence: 97%
“…Although several investigations were carried out to study the heat treatment effects on the mechanical properties of jack pine and birch [170][171][172], there is no publication available in the literature on the discoloration taking place due to the artificial weathering of the heat-treated and untreated specific wood species considered in this study. Hence, the effect of accelerated weathering on color changes of different heat-treated woods is investigated in more detail.…”
Section: Generalmentioning
confidence: 99%